Prevalence and Associated Risk Factors of Symptomatic Orthostatic Hypotension in Patients with Parkinson’s Disease - Khan, Muhammad Nawaz; Yousuf Brohi, Muhammad Hazim; Luqman, Muhammad; Rafi Ullah; Khan, Moid; Khan, Najeeb (Indus Journal of Bioscience Research, 2025)
Background: A major non-motor consequence of Parkinson’s disease (PD) that greatly increases morbidity and lowers quality of life is symptomatic orthostatic hypotension (OH). Finding the prevalence and risk factors for symptomatic OH in PD patients was the goal of this investigation. Objective: In order to enhance early detection and management techniques, it is important to ascertain the prevalence of symptomatic orthostatic hypotension in patients with Parkinson’s disease and identify risk factors that are linked to it, such as demographics, disease features, comorbidities, and drug use. Methods: The Neurology Department of a Liaquat National Hospital Karachi hosted a six-month qualitative study. Purposive sampling was used to enroll 130 PD patients in total. Semi-structured interviews and clinical evaluations were used to gather data, with an emphasis on comorbidities, medication use, illness features, and symptoms of OH. To find trends and risk variables, thematic content analysis was employed. Findings: Of the 130 participants, 46 (35.4%) had symptoms of OH. Levodopa use (87.0%), Hoehn & Yahr stage III–IV (76.1%), advanced age ≥65 years (60.9%), male gender (65.2%), disease duration >10 years (43.5%), and combination therapy (54.3%) were the main risk variables. Dizziness (82.6%), weakness (69.6%), blurred vision (52.2%), and syncope (21.7%) were among the most common symptoms. Conclusion: Almost one-third of PD patients experienced symptomatic OH, which was linked to a number of risk factors that could be changed as well as those that couldn’t. Improving patient outcomes and safety requires early detection and treatment.